PELATIHAN PEMBUATAN SOAL DENGAN MENGGUNAKAN APLIKASI GOOGLE FORM PADA GURU SD INPRES 12 PRAFI MANOKWARI - Zaki Mubarok; Mokhammad Dedi Penta Putra; Kartini Kartini; Wiska Baharuddin (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2023)
The Covid-19 pandemic has made school learning take place online, without face-to-face. Which has an impact on the implementation of the 2013 Curriculum SD Inpres 12 Prafi Manokwari has not been maximized. This problem becomes a burden as well as a challenge for students in the learning process. Teachers feel the same thing, online learning is less than optimal, because they have to learn more about technology related to the learning process and applied to elementary school students. During online learning the media used is Whatsapp. This is not optimal because the teacher only provides material and assignments with Whatsapp, then students collect the assignments again, so that the material is not sent and assignments are lost before being assessed. For this reason, the STKIP Muhammadiyah Manokwari Community Service Program (PKM) Team is trying to help increase learning technology knowledge and skills for teachers at SD Inpres 12 Prafi Maanokwari with socialization and training, including using Google Form. The use of this technology is expected to optimize online learning. In addition, it is expected to increase the interaction between teachers and students, so as to improve the ability of students and teachers to use technology.